(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
This section presents details of site location and a brief summary of the earlier investigation which recovered, among other items, nearly 10,000 artefacts, mainly quartz. The aims of the present analysis are also detailed. The original analysis was carried out a time when quartz technology was poorly understood.